Postmenopausal women - comorbid patients - Tatyana Yu. Pestrikova; Elena A. Yurasova; Olga G. Sherbakova; Marina А. Shveeva (LLC "MEDIAFORMAT", 2020)
Relevance. As the prevention and treatment of diseases improves, the average life expectancy of the population increases. For many of our contemporaries, a third of their lives are postmenopausal. Menopause-related health problems are increasingly common and require the attention of healthcare professionals. Aim. To raise awareness of gynecologists, urologists and other specialists about the medico-social significance of the problems of women in the menopausal period based on the analysis of literature sources and analysis of clinical cases. Materials and methods. To write this review, a search was carried out for domestic and foreign publications in Russian and international search systems (PubMed, eLibrary, etc.) over the past 20 years. The review included articles from the peer-reviewed literature. An analysis of 2 clinical cases with comorbid pathology in menopausal patients is presented. Results. The review presents data on age-related physiological changes and quality of life in menopausal women. The analysis of 2 clinical cases of the appointment of menopausal hormone therapy in patients with comorbid diseases was carried out. Conclusions. The importance of awareness of outpatient doctors in the diagnosis and management tactics of patients with comorbid diseases in menopause is emphasized.